1999
DOI: 10.1359/jbmr.1999.14.6.893
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of MC3T3-E1 Preosteoblast Subclones with Distinct In Vitro and In Vivo Differentiation/Mineralization Potential

Abstract: A series of subclonal cell lines with high or low differentiation/mineralization potential after growth in the presence of ascorbic acid (AA) were derived from murine MC3T3-E1 cells. Subclones were characterized in terms of their ability to mineralize a collagenous extracellular matrix both in vitro and in vivo and express osteoblast-related genes. When compared with nonmineralizing cells, mineralizing subclones selectively expressed mRNAs for the osteoblast markers, bone sialoprotein (BSP), osteocalcin (OCN),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
509
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(536 citation statements)
references
References 55 publications
17
509
2
8
Order By: Relevance
“…were similar to those of alkaline phosphatase (ALP), an osteoblast marker, 14 and bone sialoprotein (BSP), a common osteoblast differentiation marker gene, 14 especially at the late stages of differentiation (414 days; Figure 4a). The activation of the Wnt/Ī²-catenin pathway during the differentiation of MC3T3E1 cells into osteoblasts was confirmed by the induction of fibroblast growth factor 18 (Fgf18), a direct and specific target of the Wnt/Ī²-catenin pathway, 15 and by an increase in the level of Ī²-catenin (Figures 4a and b).…”
Section: Cxxc5mentioning
confidence: 56%
“…were similar to those of alkaline phosphatase (ALP), an osteoblast marker, 14 and bone sialoprotein (BSP), a common osteoblast differentiation marker gene, 14 especially at the late stages of differentiation (414 days; Figure 4a). The activation of the Wnt/Ī²-catenin pathway during the differentiation of MC3T3E1 cells into osteoblasts was confirmed by the induction of fibroblast growth factor 18 (Fgf18), a direct and specific target of the Wnt/Ī²-catenin pathway, 15 and by an increase in the level of Ī²-catenin (Figures 4a and b).…”
Section: Cxxc5mentioning
confidence: 56%
“…HA deposition is the hallmark of osteogenic differentiation in MC3T3 cell culture [67]. Silencing Runx2 and Osx over 7, 14, and 21 days produced a significant reduction in HA deposition (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…To this end, we used subclone 24 of MC3T3-E1 cells (MC-24), which were characterized originally by Franceschi as a nondifferentiating subclone of preosteoblasts. (25) While not undergoing spontaneous differentiation, like the more commonly used subclone 14 of MC3T3-E1 cells, (25) we show for the first time that this MC-24 subclone can be induced by BMP-2 to differentiate into osteoblasts that produce mineralized nodules.…”
Section: Discussionmentioning
confidence: 73%
“…(8,9) The experimental study of BMP-2 signaling and BMP responsiveness is challenging and is complicated by at least two issues: (1) cross-talk with numerous other pathways (15,16) and (2) lack of synchronization of cellular differentiation in spontaneously differentiating heterogeneous preosteoblast cultures. (25) Several studies have demonstrated that MAPKs are required for BMP-2-induction of the osteoblastic phenotype and mineral deposition in vitro. (18,21,30) In particular, the MAPK JNK is reported to be required for both late-stage spontaneous differentiation of osteoblasts and BMP-2-induced differentiation of preosteoblasts and pleuripotent cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation